A qualitative assessment of tourism research amidst COVID-19 pandemic in Pakistan - Muhammad Kashif, .; Mohd Hanafiah, Ahmad; Asma, Abdul Karim; Zeb, Alam; Mohammad Alam, . (Kuey, 2024)
The COVID-19 pandemic presents a substantial threat to Pakistan's tourism industry, precipitated by diverse factors. Scholars have shown considerable interest in researching the developments within this industry. This study presents the findings of a qualitative thematic analysis conducted on the literature pertaining to the impact of COVID-19 on Pakistan's tourism industry. Employing ATLAS.ti 9 software, a comprehensive analysis was undertaken on 22 research publications spanning the years 2020 to 2023. The results of the study reveal the emergence of six recurring themes across the literature during this period, including the need for the development of a policy framework, provision of a favorable tourism environment considering the pandemic, building consumer and employee confidence, technological innovation, stakeholder cohesion, and domestic tourism and community belongingness. Additionally, the research offers recommendations for future investigations in this domain, shedding light on the limited scholarly efforts focused on conceptualizing the growth of the tourism industry in Pakistan amidst the COVID-19 pandemic. The study also elucidates the key themes that surfaced during the analytical process.